Caste and Organization Studies: Our Silence Makes Us Complicit. Issue 9 (September 2021) - Chrispal, Snehanjali; Bapuji, Hari; Zietsma, Charlene
The caste system has received scant attention in organization studies, despite persisting over thousands of years, influencing the socioeconomic lives of over a billion people around the world and subjecting over 300 million people to severe socioeconomic discrimination. By overlooking caste, scholars risk conforming subaltern empirics to imperialist knowledge and miss the nuance and complexity that caste can bring to organization studies. We argue that the caste system is an institution that affects the workplace, yet it is difficult to dismantle because of its rooting in bodies and the sacred, which strips away agency. As an institution that is deeply embodied, caste has implications for institutional work, precarious work and modern slavery. We conclude with a call for scholarly engagement with caste to study its implications in the pursuit of grand challenges and inclusive organizations.